Erythropoietic protoporphyria in an adult with sequential liver and hematopoietic stem cell transplantation: A case report. Issue 3 (9th December 2017) - Windon, Annika L.; Tondon, Rashmi; Singh, Nathan; Abu‐Gazala, Samir; Porter, David L.; Russell, J. Eric; Cook, Colleen; Lander, Elaine; Smith, Georgeine; Olthoff, Kim M.; Shaked, Abraham; Hoteit, Maarouf; et al.
Abstract : Erythropoietic protoporphyria (EPP) is a rare inherited disorder of the heme biosynthesis pathway resulting in the accumulation of protoporphyrins in the blood, erythrocytes, and other tissues. Because of a gene mutation in the FECH gene, ferrochelatase, the enzyme involved in the final step of heme synthesis, is deficient in these patients. Although the major symptom of this disorder is photosensitivity, rarely, it can cause progressive liver disease requiring liver transplantation (LT). However, LT is not curative and only bone marrow transplantation (BMT) can correct the underlying enzymatic defect. Because liver disease results from accumulation of protoporphyrin in the liver, LT without hematopoietic stem cell transplantation leaves the new liver at risk for similar EPP‐related damage. A handful of pediatric patients undergoing sequential LT and stem cell transplantation have been described in the literature; however, to date none has been described in detail in adults. We report a case of an adult male with EPP and liver failure who successfully underwent a sequential liver and hematopoietic stem cell transplantation (HSCT). Abstract : This case report describes sequential liver and hematopoietic stem cell transplantation in an adult with liver failure and severe erythropoietic protoporphyria.